Victims, burdens, and problems: A thematic analysis of Le Journal de Montréal news coverage of Roxham Road - Clément Lechat (Facts & Frictions)
Roxham Road, a rural road in Quebec, was a longtime hotspot for migrants and asylum seekers entering Canada from the United States that the province’s news media paid close attention to, until the entry point was closed in March 2023. Scholarly research has identified frames in the coverage of this controversial crossing point between 2017 and 2019, when the number of irregular arrivals was considered a “crisis.” This article extends the research to the post-pandemic era, and during a new “crisis,” by presenting an inductive thematic analysis of 55 online news articles published in Le Journal de Montréal, the province’s most-read newspaper, throughout 2022. The results point to binary coverage that rarely speaks to migrants, and that portrays Roxham as a problem requiring policy-oriented solutions. Although aspects of the coverage remained stable in 2022, temporal and provincial specificities stand out, in particular the importance given to the French language, Quebec politics, and conflicts between the provincial and federal governments.